2019
DOI: 10.1096/fj.201802718r
|View full text |Cite
|
Sign up to set email alerts
|

Metformin treatment improves the spatial memory of aged mice in an APOE genotype–dependent manner

Abstract: Aging and apolipoprotein E4 (ApoE4) can increase the risk of cognitive impairment and neurodegenerative disorders, including Alzheimer's disease (AD), and patients with type 2 diabetes mellitus are highly susceptible to cognitive dysfunction. Recent research has indicated that metformin, a prescribed drug for type 2 diabetes, may affect cognitive function; however, findings regarding its efficacy are largely controversial. The current study reported that a 5‐mo metformin administration (300 mg/kg/d) starting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 67 publications
0
18
2
Order By: Relevance
“…The findings might explain inconsistencies in the cognitive benefits of metformin seen previously in the literature 39 . In APOE ε4 transgenic and APOE gene deficient mice, 40,41 metformin failed to activate the adenosine monophosphate kinase pathway, worsened spatial memory, and exacerbated neurodegeneration. The majority of animal or cell studies suggest that metformin can increase levels of Aβ precursor protein and β‐secretase, 42–45 or increase tau hyperphosphorylation 40,41 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The findings might explain inconsistencies in the cognitive benefits of metformin seen previously in the literature 39 . In APOE ε4 transgenic and APOE gene deficient mice, 40,41 metformin failed to activate the adenosine monophosphate kinase pathway, worsened spatial memory, and exacerbated neurodegeneration. The majority of animal or cell studies suggest that metformin can increase levels of Aβ precursor protein and β‐secretase, 42–45 or increase tau hyperphosphorylation 40,41 .…”
Section: Discussionmentioning
confidence: 76%
“…In APOE ε4 transgenic and APOE gene deficient mice, 40,41 metformin failed to activate the adenosine monophosphate kinase pathway, worsened spatial memory, and exacerbated neurodegeneration. The majority of animal or cell studies suggest that metformin can increase levels of Aβ precursor protein and β‐secretase, 42–45 or increase tau hyperphosphorylation 40,41 . We hypothesize that the interactions between metformin and the amyloid cascade in those with AD might outweigh the neuroprotective effects seen in cognitively normal people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with neuronal loss, AD pathology is characterized by the occurrence of senile plaques, which contain Aβ depositions, neurofibrillary tangles composed of hyper-phosphorylated tau, and extensive synaptic loss [6]. The sex-based prevalence of AD is well documented, with over 60% of AD patients being female [7]. An even greater sex difference has been found in the impact of AD pathology, with each additional unit of AD pathology found to be associated with a nearly 3-fold increase in the odds of clinical AD in men compared with a more than a 22-fold increase in the odds of clinical AD in women [8].…”
Section: Alzheimer's Disease and Apolipoprotein ε4mentioning
confidence: 99%
“…Each ε4 allele reduces the age of AD onset by 7 to 9 years per allele copy [12,16]. Evidence indicates that the apoE4 risk for AD is greater in women than in men [7]; a single copy of the ε4 allele in women is sufficient to increase the AD disease risk associated with two copies of ε4 in men [17]. Furthermore, it has been shown that carrying the apoE ε4 allele has a larger deleterious effect on neurodegeneration, synaptic plasticity, and adult neurogenesis, and on cognitive performance in females more than males [18].…”
Section: Alzheimer's Disease and Apolipoprotein ε4mentioning
confidence: 99%